Understanding the risk factor of food security faced by children during flood disaster in Bera, Pahang, Malaysia / Nur Farahim Abdullah - Abdullah, Nur Farahim (2016)
Food security is when all people at all times have access to adequate, safe, healthy food to sustain a healthy and active life. Food security in children expressed that the children is having adequate food daily and have a normal growth development without suffering any malnutrition. During flood situation, the food security and insecurity may happened to children due to unavoided risk factor. Bera, Pahang had been selected as the area of research as it was one of the most severe flooding district in December 2014. I n this study, the risk factor of food security faced by children during the flood disaster are being identified. Secondly is the nutritional status of the respected informant are evaluated by using the anthropometry data. The methodologies used are observation and interview with the respected victims in order to collect further information and opinion regarding the flood disaster. The selected informant consist of five female and four male from different village. The post flood questionnaires are being used to guide the responds from the informant. The data collected are being analyzed by using thematic analysis to determine the risk factor of food security associated with children. Findings showed that food supply, food choice and food intolerance may playas a vital part in food security during flood disaster. Children who move to the relocation center said that, they eat less quantity of food during flood due to the repeated menu being cooked everyday. Even though, they may eat less quantity of food than normal, their nutritional status after the flood disaster such as weight and height only had minimal differences as compared to the control subject. Most of them didn't lose any weight during and after the flood. In conclusion, even though there are risk factors associated with the food security, the effect on their nutritional status such as weight and height are minimal.